Critical-point models to relate yield and disease intensity of the multiple pathosystem in rice leaf spots disease Modelos de pontos críticos para relacionar o rendimento de grãos com a intensidade em patossistema múltiplo de manchas foliares em arroz irrigado - Bordin L.C. (2016)
© 2016, Universidade Federal de Santa Maria. All rights reserved.The occurrence of leaf spots in irrigated rice can reduce the yield and compromise the quality of the grain. However it is unknown the economic damage threshold (EDT) that these spots cause the yield of crop. The objective of this study was to obtain damage functions for models of critical, to relate damage by simultaneous occurrence of blast, brown spot and scald spot with grain yield harvests in 2011/12 and 2012/2013, in Rio do Oeste, Santa Catarina State, Brazil. Gradient of diseases intensity was generated by number of applications and fungicides rates. Design was a randomized block with four replications and six treatments consisting of mixing fungicide applications of triazole (difenoconazole) and strobilurin (azoxystrobin). In 2011/12 and 2012/13 growing season were made two and three tests respectively with the same experiment. Before each application it was determined the incidence and severity of fungal diseases. The critical point models were obtained by linear regression between grain yield and incidence (I) and severity (S). In 2011/12 the functions were not significant at the beginning of tillering and 2012/2013 harvest resulted in R=13.404-92.98I and R=10.685-3.804S. Respectively in each harvest resulted in tillering (R=9.141-103.6I; R=7.605-1.538 and R=8.864-73.91I; R=7.202-77S), panicle initiation (R=9.432-188.5I; R=7.,038-1.466S and R=10.176-87.33I; R=8.258-533.55S), booting (R=7.044-71.78I; R=6.881-1.296S and R=9.993-71.74I; R=8.846-763.83S), flowering (R=7.447-82.29I; R=8.731-1.398S and R=8.347-54.36I; R=7.338-681.52S) and milky grain (R=10.143-80.5I; R=7.522-1.402S and R=8.661-60.063I; R=9.754-1.465S). The generated functions allow getting the damage coefficient for use in the calculation of EDT in multiple pathossystem leaf spots in irrigated rice.